Towards crosslinguistic pedagogy: Demystifying pre-service teachers' beliefs regarding the target-language-only rule. (August 2020) - Woll, Nina
Abstract: The present study examines the perceived benefits of a crosslinguistic approach to language teaching, which consists essentially of promoting interaction between all of the learner's languages to facilitate additional language learning. Specifically, this paper reports on a pilot study that involved pre-service ESL teachers in Quebec (Canada) taking a foreign language course designed to foster crosslinguistic interaction, an approach which runs counter to the monolingual (target-language-only) bias of the Quebec Education Program. The key learning events of this crosslinguistic approach are intended to trigger reflections in pre-service teachers regarding their own perspective on language teaching. Preliminary findings suggest when given the opportunity to explore their multilingual repertoire, learners become aware of the positive impact of such practice on their understanding of target language features, which triggers a sense of success. Semi-directed interviews allowed to shed light on the future teachers' reflective stance regarding the potential of adopting a crosslinguistic approach to second/foreign language teaching.